BUILDING SELF IMPROVEMENT IN TEACHING PROCESS THROUGH TEACHER TALK IN EFL CLASSROOM - Rihza Galih Faturrochman; Achmad Anang Darmawan; Faishol Hadi (Journal of English Language Teaching and Islamic Integration, 2023)
English started to get recognition from very limited number of students who was granted an access to a formal education. Unlike Dutch language, Indonesian people tend to be more open since it’s not related to the colonialism language according to relationship betwEen Indonesia and British. Even after proclamation of independence, English was declared as the first foreign language due to its necessity towards international society. With the perspective of Indonesian people in general that learning English can upgrade someone’s status in the society, help to master technology and academic knowledge, and provide a better opportunity of occupation (Mappiasse & bin Sihes, 2014), English getting more attention in the learning curriculum in Indonesia. In 1989, English become a compulsory subject to be taught in the school and until today English become one of subject to be tested in national examination.